Use of Nandrolone Decanoate in Treatment of Pure Red Cell Aplasia Secondary to Diclofenac Administration: A Case Report - de Marchi, Paula Nassar [UNESP]; Sueur Vieira, André Nanny Le [UNESP]; Antunes Ribeiro, José Francisco [UNESP]; Geraldes, Silvano Salgueiro [UNESP]; Rodrigues Ramos, Paulo Roberto [UNESP]; Melchert, Alessandra [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP] (Elsevier, 2017)
Pure red cell aplasia (PRCA) is a disorder that leads to a nonregenerative anemia that results from erythroid precursors failing to reach maturity in the bone marrow, whereas the numbers of mature myeloid and megakaryocytic cells remain normal. PRCA can be induced by autoimmune processes, infections, drugs, toxins, and radiation, and is diagnosed by a bone marrow cytology examination after excluding the most common causes of nonregenerative anemia. Immunosuppressive therapies are used to treat PRCA, and usually involve the use of glucocorticoids, cyclosporin, or azathioprine. Alternatively, although little studied in veterinary medicine, drugs which stimulate bone marrow (e.g., nandrolone decanoate) have been mentioned as possible therapeutic agents. A case of PRCA that presented at the Veterinary Teaching Hospital of the Faculty of Veterinary Medicine and Animal Science (UNESP)—Botucatu, Brazil showed a good therapeutic response to weekly administration of nandrolone decanoate. Therefore, it was concluded that bone marrow stimulants might improve the quality of life of PRCA patients, provided they are used with caution and under close clinical supervision.
Keywords: aplasia; dogs; immune-mediated hemolytic anemia; nandrolone decanoate